Dendrite-free Al recycling via electrodeposition using ionic liquid electrolytes: The effects of deposition temperature and cathode surface roughness. (10th March 2021) - Wang, Yifan; Reddy, Ramana G.; Wang, Ruigang
Abstract: In this paper, the electrodeposition of Al from aluminum scrap alloys (A2020) on copper cathode substrates with varied surface roughness under different deposition temperatures was studied using low-temperature AlCl3 -1-butyl-3-methyl-imidazolium chloride (BMIC) ionic liquid electrolytes. The bulk electrodeposition of Al was carried out under a voltage of 1.5 V at a stirring rate of 120 rpm using a fixed ionic liquid electrolyte concentration (molar ratio AlCl3 : BMIC = 2:1). The effects of deposition temperature (range from 80 °C to 140 °C) and surface roughness of Cu cathode substrates (polished by 320, 600, 800, 1200 grits SiC sandpapers and mirror polishing process) on the morphology of deposited Al, current density, current efficiency and energy consumption, were investigated. The Al deposits were characterized using scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), profilometer, and electrochemical measurements for current density, current efficiency, and energy consumption. It is demonstrated that the deposition temperature and surface roughness of Cu electrodes play a critical role in the nucleation and growth of Al deposits. Higher deposition temperature promotes the diffusion and/or migration of Al2 Cl7 − ions and then enhances the current density and efficiency during the electrodeposition of Al. Smoother surface of Cu electrodes is preferred for the formation of dendrite-free Al deposits. Typically, on the mirror polished Cu electrode, no Al dendrite structure was observed, and only plate-like Al deposits were formed at the deposition temperature of 100 °C. Pure metallic Al was successfully deposited on Cu electrodes in AlCl3 +BMIC ionic liquid electrolytes for all experiments with a current efficiency range from 72% to 99% and energy consumption of 4.6–6.3 kW h/kg Al. Graphical abstract: Image 1